Educators' Motivation for Continuing Professional Learning - Beltman, Susan (Issues in Educational Research (Print), 2009)
Professionals' learning and motivation is regarded as social, situated and constructed. For successful implementation of new professional learning, consideration of both person and context is needed. Individual motivational beliefs regarding activities are, for example, inseparable from and mutually shaped by the social context in which these activities are situated. This paper reports a mixed methods study examining the relevance, effectiveness and implementation of a professional learning program, as perceived by 68 Australian educators. Participants reported enhanced personal development and valued the course, but workplace demands and limited structured support were constraints on implementation. Methodological issues associated with research in authentic professional learning settings are discussed. The study confirms the significance of exploring personal and contextual factors to gain a holistic understanding of professional learning initiatives, and to maximise their actual implementation in practice.